Pengaruh motivasi kerja dan lingkungan keluarga terhadap kesiapan kerja siswa dengan variabel moderasi self efficacy - Fatika Putri Aulia; Nimas Aulia Pambajeng Miftahunnajah (Jurnal Pendidikan Ekonomi (JUPE), 2025)
The phenomenon of the high Open Unemployment Rate among vocational high school graduates shows a mismatch between the concept of vocational education that prepares graduates to be ready to work according to their skills. This study analyzes the influence of work motivation and family environment on the work readiness of students of Accounting and Finance XI at SMK Negeri 1 Salatiga, with self efficacy as a moderating variable. The method used is a quantitative survey with a sample of 105 students through a questionnaire. Data were analyzed using SmartPLS 4.0 with the PLS-SEM model. The results show that work motivation, family environment, and self efficacy have a positive and significant influence on work readiness. However, self efficacy does not moderate the relationship between work motivation and work readiness, but has a significant effect in moderating the relationship between family environment and students' work readiness. This study emphasizes the importance of work motivation and family support, as well as the need to pay attention to psychological and social factors in preparing vocational high school graduates to face the world of work.